The interpreted sentence preceded by the beginning of the interpretation (Al-Faa) and its implications In the hadiths of Sahih Muslim: (Raparin Journal of Humanities (RJH), 2024)
This presentation aims to clarify the explanatory sentence preceded by the beginning of (Al-Faa) and the statement of its connotations in the hadiths of Sahih Muslim, the sentence is the basic rule in Arabic grammar to understand the Arabic speech from which the linguistic construction proceeds, so it is not possible to understand any linguistic fabric until after understanding and studying the sentences formed by this fabric, and the explanatory sentence is revealing the ambiguity of the sentence that precedes it, which is associated with the letter of interpretation or abstract from it, in order to push the illusion and raise the thumb, and remove the ambiguity and problem in the intended meaning, and complete Statement and clarification after the thumb to sustain the process of communication, communication and dialogue.It is clear to us through what we mentioned, that the faa is a letter of meanings, neglected non-working, useful arrangement, commentary and kindness, in addition to all that, most grammarians see that it is a letter that benefits the interpretation, and that (that) and (any) letters also benefit the interpretation, and this is what appeared to us in our study, and the student may get this meaning as a result of delving into the Arabic texts, whether in the Qur'anic expression or the hadiths of the Prophet or in poetic systems.The nature of this research necessitated its establishment on three chapters advanced introduction and preamble and sealed with the results of the research and the list of sources and references, has been singled out for the introduction to the statement of the research problem and the importance of research and mentioned previous studies and close to the research, and mentioned the research methodology, and mentioned in the preamble the definition of search terms, the first section deals with the interpreted sentence preceded by the interpretation tool (alpha), and the second section deals with the places of fulfillment interpretive in the hadiths of Sahih Muslim, and the third section deals with the explanation of hadiths and statement of their implications and the study reached a number of results, with a list of Sources and references.